Prevalence and Impact of Apolipoprotein E7 on LDL Cholesterol Among Patients With Familial Hypercholesterolemia - Tada, Hayato; Yamagami, Kan; Kojima, Nobuko; Shibayama, Junichi; Nishikawa, Tetsuo; Okada, Hirofumi; Nomura, Akihiro; Usui, Soichiro; Sakata, Kenji; Takamura, Masayuki; Kawashiri, Masa-aki (Frontiers in Cardiovascular Medicine, 2021)
Backgrounds: It has been suggested that a rare mutant apolipoprotein E7, APOE7 (p.Glu262Lys, p.Glu263Lys), has been identified in association with hyperlipoproteinemia among general population. And its prevalence has been shown as 0.005 to 0.06 %. However, no prior data exists regarding its prevalence and impact on serum lipids among patients with familial hypercholesterolemia (FH). Methods: We recruited 1,138 patients with clinically diagnosed FH (mean age = 48, male = 512, median LDL cholesterol = 231 mg/dL). We sequenced the exons of three familial hypercholesterolemia (FH) genes (LDLR, APOB, and PCSK9) and apolipoprotein E (APOE) gene. We investigated prevalence and impact on serum lipid levels of APOE7 mutant among patients with FH. Results: We identified as much as 29 patients (2.5 %) with a mutant APOE7, which is apparently much higher than that of general population. Moreover, when we focus on those without FH-mutation (n = 540), we identified 21 patients (3.9 %) with a mutant APOE7. The patients with a mutant APOE7 exhibited significantly higher median LDL cholesterol as well as triglycerides compared with those without this rare mutant (249 mg/dL vs. 218 mg/dL, p < 0.05, 216 vs. 164 mg/dL, p < 0.05, respectively). Moreover, LDL cholesterol levels in the APOE7-oligogenic FH individuals, who had a deleterious mutation in FH genes and APOE7 mutant, were significantly higher than that in monogenic FH individuals (265 versus 245 mg/dL, p < 0.05). Conclusion: We identified more patients with a mutant APOE7 than expected among patients with clinical diagnosis of FH, especially, among those without FH-causing mutation. This implies that at least a part of the patients with FH may be caused by this particular genetic mutation.